1989
DOI: 10.1007/bf01871078
|View full text |Cite
|
Sign up to set email alerts
|

Relation of ATPases in rat renal brush-border membranes to ATP-driven H+ secretion

Abstract: In the presence of inhibitors for mitochondrial H+-ATPase, (Na+ + K+)- and Ca2+-ATPases, and alkaline phosphatase, sealed brush-border membrane vesicles hydrolyse externally added ATP demonstrating the existence of ATPases at the outside of the membrane ("ecto-ATPases"). These ATPases accept several nucleotides, are stimulated by Ca2+ and Mg2+, and are inhibited by N.N'-dicyclohexylcarbodiimide (DCCD), but not by N-ethylmaleimide (NEM). They occur in both brush-border and basolateral membranes. Opening of brus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 58 publications
(71 reference statements)
6
36
0
Order By: Relevance
“…These pumps occur in two forms : an electrogenic H + -ATPase and an electroneutral H + \K + -ATPase. The plasma membrane H + -ATPases present in lower eukaryotes, such as yeast and other fungi [8,9] is described as being of the Ptype, whereas that present in several normal [10][11][12][13][14] and tumoral [15] mammalian cells is of the vacuolar (V)-type. The H + -ATPase in fungal plasma membrane functions physiologically to hydrolyse ATP and to pump H + out of the cell ; the resulting electrochemical H + gradient provides energy for an array of secondary transport systems [16].…”
Section: Introductionmentioning
confidence: 99%
“…These pumps occur in two forms : an electrogenic H + -ATPase and an electroneutral H + \K + -ATPase. The plasma membrane H + -ATPases present in lower eukaryotes, such as yeast and other fungi [8,9] is described as being of the Ptype, whereas that present in several normal [10][11][12][13][14] and tumoral [15] mammalian cells is of the vacuolar (V)-type. The H + -ATPase in fungal plasma membrane functions physiologically to hydrolyse ATP and to pump H + out of the cell ; the resulting electrochemical H + gradient provides energy for an array of secondary transport systems [16].…”
Section: Introductionmentioning
confidence: 99%
“…Intercalated cells showing H' ATPase staining: A, apically stained; B, basolaterally stained; BA, basolateral and apical pole staining; D, diffusely stained; PPA, poorly polarized apically stained; PPB, poorly polarized basolaterally stained; WPA, wellpolarized apically stained; WPB, well-polarized basolaterally stained. ent in the apical membrane (2-4), contributes to up to 40% of the overall proximal H' secretion in rat (5)(6)(7). Physiologic studies have revealed increased or reduced Na+/H+ antiport activity and bicarbonate reabsorption in the proximal tubule in response, respectively, to metabolic acidosis (8)(9)(10)(11)(12)(13)(14) or metabolic alkalosis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…the effect of membrane solubiliza tion with 0.1% DOC was examined. The ATP-binding sites of endosomal H+-ATPascs are spontaneously exposed to the extravesicular environment [24], while those of BBM H+-ATPases are hidden within the intravesicular compartment [ 14], We observed a stim ulation of the NEM-sensitive H+-ATPase ac tivity of 6.6 times upon solubilization of ves icles with DOC. indicating that the contribu tion of H+-ATPases of endosomal origin to total ATPase activity is low compared to H+-ATPases of right-side-out BBMVs (598 nmol-min-'-mg protein-1; table 2).…”
Section: H*-a Tpase Activitymentioning
confidence: 82%
“…Indeed, the Na+/H+ exchanger is thought to be inac tive at a pH above 7.2 [9], The maintenance of bicarbonate reabsorption during chronic metabolic alkalosis elevating the extracellular pH above 7.5. and the intracellular pH above 7.3-7.4 [10] may not be mediated by this exchanger, unless some compartmentation of cellular pH or an increase in the affinity of the exchanger for H+ [11] occurs within proximal cells. On the other hand, the proton pump identified in the renal cortex of different spe cies including the rat [12][13][14], pig [15] and beef [ 16] may be active at this pH. The quan titative importance of this second mechanism for bicarbonate reabsorption remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%